Organizational longevity as a predictor of organizational learning, organizational identity, organizational innovation, and fiscal conservatism - Weitzman, Felix, author; Chermack, Thomas J., advisor; Glick, Margaret B., advisor; Nimon, Kim F., committee member; McCambridge, James A., committee member (Colorado State University. Libraries, 2014)
The purpose of this study was to investigate the claims in the literature that some organizations have developed mechanisms that have increased their chances of surviving in a changing environment. The literature claimed that organizations are living entities that could learn and adapt to their business environment, have their own identities, be innovative, and exercise fiscal conservatism. The literature claimed that the organizations that could best employ these four mechanisms increased their chances of surviving the changes in the business environment that might otherwise spell their demise (Cefis & Marsili, 2005; de Geus, 2002; Elsbach & Kramer, 1996; Musso & Schiavo, 2008). This research intended to uncover whether long-lived organizations exhibit higher levels of the four factors described above, and in addition, provide analysis and synthesis of the results in the hope of helping companies live longer. This researcher hoped that a confirmation that these four factors were more pronounced in long-lived organizations than in short-lived organizations would provide both scholars and practitioners with methods to help organizations live longer. To investigate these claims, a survey instrument was designed that combined a short version of the Dimensions of the Learning Organization Questionnaire-A (Yang, 2003), the organizational identity questionnaire part designed by Albert, Ashforth, and Dutton (2000), and innovation inventory questions. Fiscal conservatism was measured by analyzing publically available data on current ratios and long-term debt. The study focused on 703 companies that were publically traded and were listed in Fortune Magazine's top 1,000 lists as of 2012. The survey was sent by e-mail to 3,900 directors and senior managers who worked in these 703 Fortune 1,000 companies. Five research hypotheses were tested to understand the relationships between organizational longevity, organizational learning, organizational identity, innovation, and fiscal conservatism. The lack of statistically significant findings, and nonresponse bias analysis, indicated that the claims that are made in the literature should be considered with caution. Until empirical evidence is found, acting on these claims, although they may have some face validity, could have serious unintended implications. The study offered some alternatives that could better predict organizational learning, organizational identity, innovation, and fiscal conservatism.
Keywords: fiscal conservatism; organizational learning; organizational innovation; organizational identity